Carbetocin vs. oxytocin at elective caesarean delivery: a double‐blind, randomised, controlled, non‐inferiority trial of low‐ and high‐dose regimens. (28th March 2022) - McDonagh, F.; Carvalho, J.C. A.; Abdulla, S.; Cordovani, D.; Downey, K.; Ye, X.Y.; Farine, D.; Morais, M.; Balki, M.
Summary: Carbetocin or oxytocin are given routinely as first‐line uterotonic drugs following delivery of the neonate during caesarean delivery to prevent postpartum haemorrhage. Low doses may be as effective as high doses with a potential reduction in adverse effects. In this double‐blind, randomised, controlled, non‐inferiority trial, we assigned low‐risk patients undergoing elective caesarean delivery under spinal anaesthesia to one of four groups: carbetocin 20 μg; carbetocin 100 μg; oxytocin 0.5 IU bolus + infusion; and oxytocin 5 IU bolus + infusion. The study drug was given intravenously after delivery of the neonate. Uterine tone was assessed by the obstetrician 2, 5 and 10 minutes after study drug administration according to an 11‐point verbal numerical rating scale (0 = atonic, 10 = excellent tone). The primary outcome measure was uterine tone 2 min after study drug administration. The pre‐specified non‐inferiority margin was 1.2 points on the 11‐point scale. Secondary outcomes included uterine tone after 5 and 10 minutes, use of additional uterotonics, blood loss and adverse effects. Data were available for 277 patients. Carbetocin 20 μg resulting in uterine tone of (median (IQR [range])) 8 (7–8 [1–10]) was non‐inferior to carbetocin 100 μg with tone 8 (7–9 [3–10]), median (95%CI) difference 0 (−0.44–0.44). Similarly, oxytocin 0.5 IU with tone 7 (6–8 [3–10]) was non‐inferior to oxytocin 5 IU with tone 8 (6–8 [2–10]), median (95%CI) difference 1 (0.11–1.89). Carbetocin 20 μg was also non‐inferior to oxytocin 5 IU, and oxytocin 0.5 IU was non‐inferior to carbetocin 100 μg. Uterine tone after 5 and 10 minutes, use of additional uterotonics, blood loss and adverse effects were similar in all groups.